Amide cluster induced and hydrogen bonding regulated luminescence of linear aliphatic polyamide 1212 with a long alkane chain. Issue 5 (6th January 2023) - Yan, Xinjin; Wei, Meng; Miao, Xu; Qiao, Xiaoguang; Zhang, Xiaomeng; Fu, Peng; Pang, Xinchang; Liu, Minying; Zhao, Qingxiang; Chen, Shuang; Cui, Zhe
Abstract : PA1212 exhibits blue fluorescence and persistent room-temperature green phosphorescence. Hydrogen-bond-constructed amide clusters play an important role in the emission. The order and extension of the hydrogen bonds regulate the luminescence process. Abstract : Luminescence of non-conjugated polymers attracts much attention due to its importance in fundamental and applied research. At present, however, the research on nonconventional luminescent polymers (NLPs) in terms of both the structure regulation and emission mechanism seems to be still in its infancy. Herein, we report for the first time that PA1212, a representative engineering plastic with the longest saturated carbon chain among commercial polyamides, is an efficient NLP, which exhibits dual emission of blue fluorescence and persistent room-temperature green phosphorescence as well as high quantum yield (∼13%). Systematic photophysical characterization demonstrates the important role played by hydrogen-bonded amide groups in the emission, and the emission intensity shows a clear linear positive correlation with the amide clusters constructed from ordered hydrogen bonds in the crystalline region. Moreover, PA1212 in the α form with linearly extended hydrogen-bonded clusters exhibits longer emission wavelengths than in the γ form, owing to the narrower band gap between the valence band maximum and the conduction band minimum. Further variable temperature fluorescence studies reconfirm the amide cluster-triggered emission (CTE) mechanism of PA1212, and show the possibility of application of fluorescence spectra in the study of polyamide aggregation states. This work not only deepens the understanding of CTE, but also provides a new strategy to regulate the luminescence of polyamides, and meanwhile, highlights the application prospects of luminescent polyamides.